IMPLEMENTASI PEMBELAJARAN BLENDED LEARNING DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH ATAS ISLAM HASYIM ASY’ARI KOTA BATU - Bryen Yuzac Zein Baneka Ranti; Mohammad Hanief; Atika Zuhrotus Sufiyana (VICRATINA, 2021)
The implementation of blended learning is a new learning method applied by teachers and students at Madrasah Aliyah Hasyim Asy'ari Batu City. The focus of the research is on planning, implementing and evaluating blended learning. In this study, the researcher used a phenomenological-based qualitative approach using case study research. The researcher revealed that there were several research results, namely blended learning planning starting from the preparation of materials, e-learning formats, and evaluation. The application of this research starts from offline and online learning, introduction, application implementation and learning evaluation. For the evaluation, the researcher also revealed that there was a provision of school facilities that facilitated the implementation of blended learning.